Modelling and optimizing of electronic toll collection (ETC) at Malaysian toll plazas using microsimulation models - E. Jehad, A; Ismail, A; N. Borhan, M; Z. Ishak, S (International Journal of Engineering and Technology, 2018)
Toll plazas are one of the critical components of a roadway system. At the same time, they are among the most complex road structures, as drivers are exposed to a large amount of information and have a short amount of time to make a decision to avoid any collision. VISSIM and SSAM are used to investigate the effect of various Malaysian toll plazas design and traffic conditions on driversâ€™ behaviour and level of safety. The study was made a well-calibrated and validated VISSIM simulation model and several scenarios were simulated to test their efficacy for improving toll plaza safety aspects by using SSAM afterwards. From the results it was observed that the VISSIM simulation model scenarios such as implementing booths orientation and segregating lanes for different vehicle types to improve the level of service have significant safety aspects improvement regarding conflict points and lane change accidents results while using Surrogate Safety As-sessment Model (SSAM) in order to give the need for remediation of either the roadway design or the flow-control strategy.Â Â
Keywords: Safety; Toll Plaza; Microsimulation; VISSIM; SSAM; Traffic Management